Cross-national differences in willingness to believe conspiracy theories. (October 2022) - Hornsey, Matthew J.; Pearson, Samuel
Abstract: Conspiracy beliefs are not just generated by "under-the-skull" individual factors, but are shaped also by cultural, economic, and institutional realities. A scan of the literature—complemented by our own secondary data analyses—suggests a reasonable convergence of evidence that conspiracy beliefs are higher in nations that are more corrupt, more collectivist, and lower in GDP per capita. There is some evidence that conspiracy beliefs may also be shaped by economic inequality, power distance, and authoritarianism, although the evidence base is thin. We also review literature that examines how individual correlates of conspiracy beliefs vary across nations. We discuss challenges associated with conducting international research on conspiracy beliefs and chart a future research agenda for creating truly global insights into conspiracist thinking.